Case Study of Learning Difficulty Class III Students at SDN 06 Batu Taba, Ampek Angkek Sub-District - Ananda, Dea; Rahmi, Alfi; Sabarrudin, Sabarrudin (Darul Yasin Al Sys, 2023)
Diagnosis of learning difficulties is the process of determining the problem of students' inability to learn by examining the background causes by analyzing the symptoms of learning difficulties or barriers that appear. The purpose of this study is to identify the location of learning difficulties experienced by students and the provision of treatment. The type of research used in this research is a qualitative case study in nature. The key informants in this study were students with the initials S and supporting informants, namely the school principal, who was also a class III homeroom teacher, class II teacher, and parents of students. Data collection techniques were carried out using non-test methods, namely observation, interviews, general problem-solving tools, problem-solving tool PTSDL, Sociometry, and format of mastery of learning material difficulties. The data analysis technique is data triangulation. This study found that one student with the initial S experienced learning difficulties in mathematics and Arts and Culture and Skills. After being given counseling services in the form of remedial learning, students with the initial S experienced an increase in subject mastery.